Door in door out and transportation times in 2 telestroke networks. Issue 1 (February 2019) - Al Kasab, Sami; Almallouhi, Eyad; Harvey, Jillian; Turner, Nancy; Debenham, Ellen; Caudill, Juanita; Holmstedt, Christine A.; Switzer, Jeffrey A.
Abstract : Background: Inter-hospital transfer is important in the treatment of acute stroke. We sought to assess door in to door out (DIDO) time at spoke sites, and transportation time between spoke sites and thrombectomy-capable stroke center (TSC) in 2 large, rural telestroke networks. Methods: Records of patients treated with tissue plasminogen activator through 2 telestroke networks between March 2017 and December 2017 were reviewed. Mann–Whitney test was used to compare median times, and a generalized linear regression model was used to predict the total time of care controlling for transportation distance. Results: Eighty-five patients were included with median NIH stroke scale on presentation of 13 (interquartile range [IQR] 7–17), median door to needle time 49 minutes (IQR 40–62), and median DIDO 111 minutes (IQR 92–157). Eighteen patients (21%) underwent computed tomography angiography (CTA) at spoke prior to transportation. Median DIDO was 169 minutes for patients who received CTA before transfer, compared with 107 minutes for patients who did not ( p = 0.0004). Median door-to-groin time at TSC was 68 minutes for the CTA group and 85 minutes in the non-CTA group ( p = 0.832). Controlling for distance, the predicted time of care from spoke door in time to groin puncture at TSC (sDTG) is 93.68 minutes longer for patients who receive CTA prior to transport ( p = 0.034). Conclusion: In the included telestroke networks, the sDTG time is longer when CTA is conducted at spoke site prior to transportation to TSC. New strategies are urgently needed to decrease sDTG when CTA is done prior to transfer to TSC.